Ultrasonic evaluation of mass concrete subjected to isothermal curing - Sazon, Patrick Junther R.; Antonio, Oscar Victor M. Jr. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
The study aimed to know the effect of isothermal curing in the damages formed in mass concrete. Linear and nonlinear ultrasonic methods in nondestructive testing were performed to evaluate the mass concrete specimens subjected to isothermal curing. The ultrasonic methods were the ultrasonic pulse velocity test, the ultrasonic wave attenuation analysis, the frequency content analysis, the Scaling Subtraction Method, and the Harmonic Generation Method. Mass concrete specimens were subjected to the ultrasonic tests before and after subjecting them to compression using the universal testing machine. Comparisons between the results from the normally cured specimens and the isothermally cured specimens were more apparent than that in the normally cured specimens. Therefore, it was proven that control measures are required to prevent or reduce the progression of damage due to isothermal curing.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: High strength concrete -- Testing; Ultrasonic testing